The Wealth of Today and Tomorrow - World Bank (Washington, DC: World Bank, 2021)
Good education for all is the key to a better long-term future for the Sahel region. Education improves employability and incomes, narrows gender gaps, lifts families out of poverty, strengthens institutions, and yields benefits that echo to the next generation. The good news is that the region has taken the important first steps toward building this future. Many more children have been able to access education over the past 15 years: enrollment in the region has nearly doubled in primary education and tripled in secondary education. And governments have launched numerous initiatives and announced high-level commitments in support of education. Still, many children remain out of school, and those who are in school learn far less than they should. Of the region’s primary-school-age children, 40 percent are out of school. Furthermore, the region’s learning poverty rate is 88 per-cent—meaning that only 12 percent of children are enrolled in school and able to read and comprehend an age-appropriate passage by late primary age. Access is lower at other levels of education: enrollment is below 56 percent in lower secondary throughout the Sahel G5 and between 2 and 10 percent in pre-primary and tertiary. All these contributing factors result in low education attainment in the Sahel region and therefore low productivity. In Niger, for example, 72 percent of current working-age adults have no education at all. In every Sahel country, fewer than 50 percent of adult females are literate, compared with 59 percent in Sub-Saharan Africa as a whole and 80 percent in low- and middle-in-come countries. This figure drops to 23 percent for females living in the Sahel rural areas. Even among the youngest segment of the labor force—youth aged 15-24, reading and writing performance in the Sahel is relatively low, with literacy rates ranging from 45 to 66 percent, while the average in Sub-Saharan Africa is 77 percent. Additionally, the poorest children and youth, and those affected by conflict, who most need a good education to have a chance in life, suffer the most from failings in education access and quality. The upper secondary enrollment rate is only 5 percent for the poorest rural girls, versus 100 percent for urban boys in the wealthiest quintile.